Mekanisme Perhitungan, Penyetoran dan Pelaporan Pajak Penghasilan (PPh) Pasal 21 Pegawai/Karyawan pada Hotel Mahamaya - Baiq Karmila Susanti; Nurabiah (Jurnal Aplikasi Perpajakan, 2026)
The purpose of preparing this Field Work Practice (Internship) Report is to directly understand the process of calculating, depositing, and reporting Article 21 Income Tax (PPh Pasal 21) at Hotel Mahamaya, as well as to comprehend the application of the Average Effective Rate (TER) through the Coretax Administration System (Cortex). This objective was achieved through an internship of approximately four months by participating in all activities within the Accounting and Tax Department, allowing the author to observe and practice the tax administration procedures implemented by the company. The results show that the management of PPh Pasal 21 at Hotel Mahamaya has been carried out in accordance with applicable regulations, starting from collecting and validating employee salary data, calculating the tax using the TER method, preparing withholding slips, and submitting the monthly tax return (SPT Masa) through the Cortex system. This workflow involves coordination between HRD, Accounting, and Tax to ensure the accuracy of each employee’s income data before it is entered into the system. After all data is verified, the tax division proceeds with issuing withholding slips, generating the billing code, depositing the tax, and completing the submission of the PPh Pasal 21 monthly return. By following all these stages, the author gained an understanding that PPh Pasal 21 administration requires precision, accurate data management, and the use of digital systems to ensure that tax reporting is carried out effectively and in compliance with regulations.